30 EARS ANNIVERSARY OF BELARUSSIAN METALCORD - E. V. Shamanovskaya; E. V. Ragozin (Литьë и металлургия)
The article describes the history of the formation and development of metal cord production in Belarus. The main ways of the Belarusian metallurgical works had followed from the production of the first tons of steel wire cord, before reaching the production capacity, twofold of the design capacity. The authors paid a lot of attention to the structure of hardware production, which is the visiting card of the plant today, to people who directly participated and promote the process of new products manufacture. Particular attention in the article is devoted to the geography of deliveries of metal cord and the main customers – consumers who use this product in the production of tires. The changes in the properties of the steel wire cord from the moment of first manufacture to the present time is traced, based on permanent changes of the requirements of the automotive industry.